Intervención en habilidades sociocognitivas para la solución de problemas interpersonales en población infantil con TDAH: Un ensayo controlado aleatorizado. - Russo, Daiana; Bakker, Liliana; Rubiales, Josefina; Lacunza, Ana B. (Revista de Psicopatologia y Psicologia Clinica, 2025)
Objective: To enhance sociocognitive skills for interpersonal problem-solving in children with ADHD. Method: A randomized controlled trial, with pre- and post-intervention assessment, was used. The sample consisted of 40 children randomly assigned to either the intervention (n = 20) or the waiting list control group (n = 20), aged from 8 to 10 years, selected for exhibiting a diagnosis of ADHA. Results: Overall, significant improvements were found from pre- to post-treatment in the intervention group, with an increase in scores on most interpersonal problem-solving skills and assertiveness, and a decrease in scores on negative social skills. According to parental reports, improvements were also observed in basic social skills and interpersonal problemsolving abilities. Conclusions: The implemented program promoted improvements in cognitive skills for interpersonal problemsolving and perception of social performance, with implications at both the individual level for emotional and social well-being.